If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x * x + 27 = 0 Multiply x * x 3x2 + 27 = 0 Reorder the terms: 27 + 3x2 = 0 Solving 27 + 3x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3x2 = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 3x2 = 0 + -27 3x2 = 0 + -27 Combine like terms: 0 + -27 = -27 3x2 = -27 Divide each side by '3'. x2 = -9 Simplifying x2 = -9 Reorder the terms: 9 + x2 = -9 + 9 Combine like terms: -9 + 9 = 0 9 + x2 = 0 The solution to this equation could not be determined.
| 3c^2=-16c+5 | | n+40=11q+9 | | 2m+3=7 | | 4(m+2)=40 | | 3x^3+25x^2+8x=0 | | g/2+3=15 | | 3a+12=38 | | 0.50X+0.45(40)=0.25(150) | | 3x+4=2x-24 | | 2x(x-5)=3 | | 3t-24=57 | | 8x+9=-143 | | 3v+17=35 | | 4v+14=32 | | 12+4x-8=48 | | ad= | | y=x^3-27x+4 | | 6(4-8a)+7=-17 | | -3x^2+8x-2=0 | | (7)(4+2x)=56 | | 64m^8-49n^6=0 | | -(9x-8)= | | -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r |